Land use changes in Southern Croatia (Dalmatia) since the beginning of the 20th century - Anđela Vrkić; Ante Blaće (Acta Geographica Slovenica)
This research analyzed land use changes in Southern Croatia over the past 120 years. The methodological approach employed analysis and chronological comparison of archival and statistical data, and geoprocessing of the Corine Land Cover geodatabase. In the period spanning from 1900 to 1945, agriculture was the main activity, accompanied by a notable decline in vineyards. The subsequent era, from 1945 to 1991, was characterized by the dominance of rapid industrialization, onset of land abandonment, and the reversion of former agricultural areas to natural vegetation. Since 1991, the trend of land abandonment and deruralization has persisted and intensified. As a result, shrubs and forests now claim the largest share of the researched area, solidifying a new landscape configuration.